2023
DOI: 10.1021/acs.est.2c03998
|View full text |Cite
|
Sign up to set email alerts
|

Replacement Flame-Retardant 2-Ethylhexyldiphenyl Phosphate (EHDPP) Disrupts Hepatic Lipidome: Evidence from Human 3D Hepatospheroid Cell Culture

Abstract: The present study aims to evaluate the effects of repeated exposure to 2-ethylhexyldiphenyl phosphate (EHDPP) on human liver cells. In vitro three-dimensional (3D) hepatospheroid cell culture was utilized to explore the potential mechanisms of EHDPP-mediated metabolic disruption through morphological, transcriptional, and biochemical assays. Lipidomics analysis was performed on the individual hepatospheroids to investigate the effects on intracellular lipid profiles, followed by hepatospheroid morphology, grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 67 publications
1
4
0
Order By: Relevance
“…Specifically, the study identified disruptions in lipid metabolism induced by TPhP, characterized by an increase in triglycerides (TGs) and a decrease in Cer and SM species, among other alterations. In another study, similar lipid disruption profiles were found for EHDPP in HepG2, confirming the adipogenic behavior induced by the OPE family . Concerning cell death induction, a work by Yu et al explored the toxicity of OPEs on A549 cells and reported that TPhP is one of the most cytotoxic OPE compounds .…”
Section: Resultssupporting
confidence: 59%
See 1 more Smart Citation
“…Specifically, the study identified disruptions in lipid metabolism induced by TPhP, characterized by an increase in triglycerides (TGs) and a decrease in Cer and SM species, among other alterations. In another study, similar lipid disruption profiles were found for EHDPP in HepG2, confirming the adipogenic behavior induced by the OPE family . Concerning cell death induction, a work by Yu et al explored the toxicity of OPEs on A549 cells and reported that TPhP is one of the most cytotoxic OPE compounds .…”
Section: Resultssupporting
confidence: 59%
“…In another study, similar lipid disruption profiles were found for EHDPP in HepG2, confirming the adipogenic behavior induced by the OPE family. 51 Concerning cell death induction, a work by Yu et al explored the toxicity of OPEs on A549 cells and reported that TPhP is one of the most cytotoxic OPE compounds. 52 Also, preliminary results of another study in our laboratory show that the exposure of A549 cells to TPhP causes a higher level of cell death than other OPEs at the same concentration (data not published).…”
Section: Resultsmentioning
confidence: 99%
“…The alterations in lipid homeostasis induced by the OPEs were also observed in several previous studies. For instance, treatment with 10 μM EHDPP led to a significant increase in the concentrations of glycerophospholipids such as PE and PI and decreased the total concentrations of Cer and SM in human liver cells . Exposure to TPHP for 48 h increased TG, PA, and Cer levels but decreased SM and PE levels in JEG-3 cells .…”
Section: Resultsmentioning
confidence: 98%
“…For instance, treatment with 10 μM EHDPP led to a significant increase in the concentrations of glycerophospholipids such as PE and PI and decreased the total concentrations of Cer and SM in human liver cells. 16 Exposure to TPHP for 48 h increased TG, PA, and Cer levels but decreased SM and PE levels in JEG-3 cells. 44 Moreover, a recent epidemiological study reported that serum levels of tripropyl phosphate (TPrP) and tri-n-butyl phosphate (TnBP) presented negative correlations with PG (18:0) and positive correlations with PI (18:1/22:2), 45 which further supports our findings of lipid metabolism dysfunction induced by OPEs in silver carp.…”
Section: Opes-induced Changes In Hepatic Lipidmentioning
confidence: 88%
See 1 more Smart Citation